Evaluation of drug promotional literatures in a tertiary care hospital setting in South India - Kudthni, Ravi H.; Ahmed, Fazeel Zubair; Madanna, Sangala Srimanth; Derangula, Samba Siva Raju; Kumar, Pothuru Anil (International Journal of Basic & Clinical Pharmacology, 2021)
Background: The drug promotional literature is one of many sources for seeking information about the drugs to the busy medical practitioner. The aim of current study was to assess drug promotional literatures as per world health organization, criteria and categorize them and to analyse the claims in presented in DPL. Methods: Current study is a descriptive study in which pharmaceutical promotional materials were collected from selected out-patient departments of a tertiary care hospital, Kurnool. Printed drug promotional literatures for modern drugs were collected and an assessment was made whether the advertisements adhered to WHO criteria for medicinal drug promotion. Results: A total of 271 drug promotional literatures were collected. Information about the single drug was given in 127 (46.9%). 144 (53.1%) DPLs contain fixed-dose combination. Majority of drug promoted in collected DPLs were miscellaneous group 83 (30.8%) followed by antimicrobials 55 (20.3%) and blood and cardiovascular drugs 37 (13.1), gastrointestinal drugs 23 (8.5%), drugs acting on endocrine system 23 (84.5%). Generic name was mentioned in 229 (84.5%) while brand name was mentioned in 271 (100%) of DPL. Conclusions: The study concluded that the drug information provided in the promotional brochures can be incomplete and unreliable. Hence a physician should not rely solely on the DPL provided by medical representatives. All brochures circulated among prescribers must undergo a strict process of assessment regarding information provided, especially related to efficacy and safety.